2017
DOI: 10.1007/s12192-016-0744-y
|View full text |Cite
|
Sign up to set email alerts
|

HSP70 in human polymorphonuclear and mononuclear leukocytes: comparison of the protein content and transcriptional activity of HSPA genes

Abstract: Cell-type specific variations are typical for the expression of different members of the HSP70 family. In circulating immune cells, HSP70 proteins interact with units of signaling pathways involved in the immune responses and may promote cell survival in sites of inflammation. In this work, we compared basal HSP70 expression and stressinduced HSP70 response in polymorphonuclear and mononuclear human leukocytes. The intracellular content of inducible and constitutive forms of HSP70 was analyzed in relation to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…Boyko et al found an increased expression of stressinducible proteins including HSPs in neutrophil granulocytes in humans. 36 In all species, the total blood neutrophil pool (TBNP) is divided into the circulating neutrophil pool (CNP) and the marginal neutrophil pool (MNP). While the CNP represents the quantitated neutrophil count derived in the routine WBC (white blood count), the MNP is a hidden population, which is associated to the vascular endothelium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Boyko et al found an increased expression of stressinducible proteins including HSPs in neutrophil granulocytes in humans. 36 In all species, the total blood neutrophil pool (TBNP) is divided into the circulating neutrophil pool (CNP) and the marginal neutrophil pool (MNP). While the CNP represents the quantitated neutrophil count derived in the routine WBC (white blood count), the MNP is a hidden population, which is associated to the vascular endothelium.…”
Section: Discussionmentioning
confidence: 99%
“…The differences between species can possibly be explained with the different‐sized compartments of neutrophil granulocytes in the blood of cats and dogs. Boyko et al found an increased expression of stress‐inducible proteins including HSPs in neutrophil granulocytes in humans 36 . In all species, the total blood neutrophil pool (TBNP) is divided into the circulating neutrophil pool (CNP) and the marginal neutrophil pool (MNP).…”
Section: Discussionmentioning
confidence: 99%
“… 29 30 The HSP and insulin signalling-related gene expression will be determined from polymorphonuclear cells. 31 …”
Section: Methods and Analysismentioning
confidence: 99%
“…High-sensitivity shotgun mass spectrometry will be used to characterise the lipidome of plasma and polymorphonuclear blood cells 29 30. The HSP and insulin signalling-related gene expression will be determined from polymorphonuclear cells 31…”
Section: Methods and Analysismentioning
confidence: 99%
See 1 more Smart Citation